Intensity through the Objects in Jorge Luis Borges’ Poetry - Espejo Ibáñez, Nestor (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Borges’ poetry establishes a close relationship with memory. It goes over references and elements that built a specific vitality. This paper aims to reflect on three objects through the concept of intensity. The purpose here is to demonstrate how Borges’ poetics is the result of an exhaustive process of creation. For this, a literature review was made from some critical and biographical sources about the treatment of the knife, the book, and the mirror with respect to memory. This approach shows a journey between lived experiences and the ways in which these objects are presented and connected to a personal or national memory. Borges raises a poetic force from allegory and memory. The intensity in the reconstruction of the object suggest a type of a reader that, far from age or time, becomes part of the poem.